Menjaga kelestarian koleksi bermuatan lokal melalui pengelolaan Muhammadiyah Corner di Universitas Muhammadiyah Prof. DR. HAMKA - Jalinur, Jalinur; Apriyanto, Mifta; Marta, Difa Artu; Afroda, Helmi (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2024)
Purpose. The Muhammadiyah Corner, a feature of the Muhammadiyah College Library, serves as a valuable resource for patrons. Its local content collection plays a vital role in promoting Islamic culture, history, and Muhammadiyah values. Effective preventive measures are needed to manage and preserve this collection. Hence, this study seeks to investigate the management of local content collections and their preventive measures in the Muhammadiyah Corner of the Universitas Muhammadiyah Prof. Dr. HAMKA library.Methodology. This research uses a qualitative case study approach, and case study data was collected from various relevant sources. Data collection methods include interviews, observation, and document analysis. This data analysis technique is data organization, reading, describe data into codes and themes, classifying data into codes and themes, interpret data, and present and visualize data.Results and discussion. This study revealed issues in managing Muhammadiyah Corner's local content at Universitas Muhammadiyah Prof. Dr. HAMKA library, namely collection management, the implementation of preventive measures, and policies and guidelines. Muhammadiyah Corner's local content can provide significant benefits in preserving intellectual heritage, building institutional identity, supporting research and learning, preventing library material damage, and developing relevant services for the entire academic community.Conclusions. This research indicates that Universitas Muhammadiyah Prof. Dr. HAMKA library has taken preventive steps regarding Muhammadiyah Corner's local content but needs to maximize these efforts to ensure the proper maintenance of Muhammadiyah Corner's muatan lokal and provide valuable information to library users, and crucial step in supporting the broad development of science.